Hermeneutika Kidung Pantun Sunda - Wiradiredja, M. Yusuf (LP2M ISBI Bandung, 2021)
Cultural expression, especially art, in many ways has a very strong relationship with the cosmology, space, or environment in which expression is born. In other words, cultural products, especially works of art that are rarely affected by the surrounding natural conditions. In the context of a popular Sundanese song, it is impossible for Koko to compose the song